Day 1 Wed, September 14, 2016 2016
DOI: 10.2118/180307-ms
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Wellbore Stability Evaluation for Deepwater Drilling During Tripping

Abstract: This paper identifies wellbore stability concerns caused by transient surge and swab pressures during deepwater drilling tripping and reaming operations. Wellbore stability analysis is presented that couples transient surge and swab wellbore pressure oscillations and in-situ stress field oscillations in the near wellbore (NWB) zone in deepwater drilling. Deepwater drilling is usually subjected to narrow drilling windows and significant wellbore pressure oscillations during tripping/reaming becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Excessive pressure variation in the wellbore can create instability and other drilling problems. Accurate prediction of pressure variation is vital for estimating the maximum tripping or reaming speeds to keep the pressure in the wellbore within specified limits of the safe operational window [34] [35].…”
Section: Preventive Measures For Wellbore Stability Problemsmentioning
confidence: 99%
“…Excessive pressure variation in the wellbore can create instability and other drilling problems. Accurate prediction of pressure variation is vital for estimating the maximum tripping or reaming speeds to keep the pressure in the wellbore within specified limits of the safe operational window [34] [35].…”
Section: Preventive Measures For Wellbore Stability Problemsmentioning
confidence: 99%
“…The variation of maximum surge pressure and swabbing pressure at each depth within the wellbore with time were predicted proposed solving the transient surge pressure of each passage using the mixing implicit feature line method, which obtained the numerical solutions of transient surge pressure under various conditions [27]. To acquire the wellbore pressure and ground stress field in the near-wellbore section of deepwater drilling, some scholars proposed a method for analyzing wellbore stability based on the oscillation coupling of transient surge pressure [28]. Considering the liquid-solid twophase medium, researchers studied the transient surge pressure during tripping operations with the use of the numerical simulation method [29].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional methods used to assess the wellbore stability analysis generally assume that the loads acting on the wellbore are in steady-state [1][2][3]. Nonetheless, recent researches have revealed that the magnitudes of the loads affecting the wellbore stability are more likely to change over time; therefore, the wellbore pressure is prone to fluctuations [4,5]. The drill string vibration cyclic load is one of the most common sources of wellbore pressure fluctuations and numerous researches have demonstrated its impact on wellbore stability: ref.…”
Section: Introductionmentioning
confidence: 99%